Bioequivalence Study of Two Oral Formulations of Irbesartan 300 mg in Healthy Volunteers - Cánovas, M.; Cabré, F.; Polonio, F. (Drug Research, 2014)
A bioequivalence study of 2 irbesartan (CAS 138402-11-6) film-coated tablet formulations was carried out in 40 healthy volunteers according to an open label, randomized, 2-period, 2-sequence, crossover, single dose and fasting conditions design. The test and reference formulations were administered in 2 treatment days, separated by a washout period of 7 days. Blood samples were drawn up to 96 h following drug administration. Plasma concentrations of irbesartan were obtained by a validated HPLC method using MS/MS detection. Log-transformed AUC0–t and Cmax values were tested for bioequivalence based on the ratios of the geometric LSmeans (test/reference). tmax was analysed nonparametrically. The 90% confidence intervals of the geometric LSmean values for the test/reference ratios for AUC0–t (98.06–109.48%, point estimator 103.61%) and Cmax (88.93–100.87%, point estimator 94.72%) were within the bioequivalence acceptance range of 80–125%. According to the European Guideline on the Investigation of Bioequivalence it may be therefore concluded that test formulation of irbesartan 300 mg film-coated tablet is bioequivalent to the reference formulation. Overall, it was judged that the study was conducted with a good tolerance of the subjects to both study drugs.
Keywords: antihypertensive drugs; bioequivalence; CAS 138402-11-6; irbesartan; pharmacokinetics